Effect of planting time, day length, soil pH and soil moisture on onion - S.M. Rezaul Karim; Ibrahim N.R (2013)
This paper describes the impacts of planting time, day length, soil pH, and soil moisture on growing of onion. Planting time for onion is different across the countries due to seasonal variations. In Bangladesh, optimal time for planting is late of October in winter season but end of December for summer varieties; in India, mid of November (cv. Pusha Madhavi), in Pakistan, 3 rd December to 4th January (cv. Robina), while in Sudan, between mid October to mid November. Most of the onion cultivars are short-day plant, which need photoperiod of 12 h but other long-day varieties require 13.5 to 14.0 hr. The optimal soil pH for onion crop is 6.2 to 6.8 with the sandy loam types of soil. The actual requirement of soil moisture is difficult to determine because it depends on the types of soil, temperature and day length received by the crop. However, proper irrigation scheduling and types of irrigation system can help to maintain appropriate soil moisture in onion